2019
DOI: 10.2139/ssrn.3478694
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and the Financial Services Sector – How to Achieve New Heights

Abstract: Institute's reputation for quality, integrity and nonpartisanship is its chief asset. Its books, Commentaries and E-Briefs undergo a rigorous two-stage review by internal staff, and by outside academics and independent experts. The Institute publishes only studies that meet its standards for analytical soundness, factual accuracy and policy relevance. It subjects its review and publication process to an annual audit by external experts. As a registered Canadian charity, the C.D. Howe Institute accepts donation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…As numerous C.D. Howe Institute studies have demonstrated, enhanced productivity is a critical driver of long-term economic growth (see, for example, Omran and Kronick 2019). Gains in Canadian living standards rely primarily on labour productivity growth.…”
Section: Is the Abf Industry For "Real"?mentioning
confidence: 99%
“…As numerous C.D. Howe Institute studies have demonstrated, enhanced productivity is a critical driver of long-term economic growth (see, for example, Omran and Kronick 2019). Gains in Canadian living standards rely primarily on labour productivity growth.…”
Section: Is the Abf Industry For "Real"?mentioning
confidence: 99%